ANALISIS MODEL LAYANAN KREDIT LEMBAGA KEUANGAN MIKRO BAGI UMKM GUNA MENINGKATKAN KINERJA UMKM DI KABUPATEN KLATEN - Retnoningrum & Sri Hutami (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2015)
UMKM are economic actors and subjects especially vital in the construction of the expansion of opportunities for new entrepreneurs, employment and reduce unemployment (pro-job). UMKM directly related to life and increased prosperity for Indonesian people (pro-poor). Optimally of UMKM should be supported for the provision of assistance in the form of facilities and infrastructure institutionalized financial to support productive activities. In 2005, Government launched the National Credit Year with the goal of ensuring equal opportunities associated with micro-credit among the various groups, that efforts of government in overcoming barriers to financial aid UMKM, one of which microlenders is the Lembaga Keuangan Mikro (LKM). This study was conducted to analyze the suitability of the service model of LKM loans to the performance of UMKM. Respondents were 166 UMKM in Klaten, using Structural Equation Model (SEM) AMOS 18, the analysis was conducted on the suitability test models, test convergent validity and causality test models. The results showed that the model fit and micro-credit services have a significant effect on the performance of UMKM. Keywords: UMKM, credit, performance